In silico discovery of potential uridine-cytidine kinase 2 inhibitors form the rhizome of Alpina mutica - Malami, Ibrahim; Abdul, Ahmad Bustamam; Abdullah, Rasedee; Kassim, Nur Kartinee; Waziri, Peter M.; Etti, Imaobong Christopher (M D P I AG, 2016)
Uridine-cytidine kinase 2 is implicated in uncontrolled proliferation of abnormal cells and it is a hallmark of cancer, therefore, there is need for effective inhibitors of this key enzyme. In this study, we employed the used of in silico studies to find effective UCK2 inhibitors of natural origin using bioinformatics tools. An in vitro kinase assay was established by measuring the amount of ADP production in the presence of ATP and 5-fluorouridine as a substrate. Molecular docking studies revealed an interesting ligand interaction with the UCK2 protein for both flavokawain B and alpinetin. Both compounds were found to reduce ADP production, possibly by inhibiting UCK2 activity in vitro. In conclusion, we have identified flavokawain B and alpinetin as potential natural UCK2 inhibitors as determined by their interactions with UCK2 protein using in silico molecular docking studies. This can provide information to identify lead candidates for further drug design and development.